PENGARUH BAURAN RITEL TERHADAP KEPUTUSAN PEMBELIAN PADA MINIMARKET MELATI DI KECAMATAN DUKUN GRESIK - TRIAS RAHMAWATI, DESY (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Modern era makes kind of human need and wants more and more increase every time. This modern era have the impact to human live to be more practis, quick,and economics. This fact changes style of buying in village society more pleasure buying in modern market than buying in traditional market. Buying in modern market makes them buy something so practis and quick. Because of that modern ritel increase, not only in the big city but also in the rular to fulfill all of human needs. This research is a quantitative research with a survey approach to determine the influencet of retailing mix towards buying decision in Melati Minimarket. This research is done at 205 respondents to do assumption classical test and hypothesis test. The result of F-test show as big as 36,279 and supported by the signification value 0,000 which is indicated that there simultaneously there is an influence of retailing mix towards buying decision in Melati Minimarket. The result of t-test partially indicated that variables product(X1), price(X2), promotion(X3), service(X4), and physical fasilities(X5) have significant influence of retail mix towards buying decision in Melati Minimarket, The value of Adjusted R Square 0,464 means that retailing mix influence of buying decision in Melati Minimarket as big as 46,4% while the remainingas big as 53,6% are influenced by the other variables outside of this research. Key Words : Retailing Mix, Buying Decision